Neck strength assessment offers no clinical value in predicting concussion in male professional rugby players: a prospective cohort study - Liston, M.; Leckey, C.; Whale, A.; van Dyk, N. (Journal of Orthopaedic & Sports Physical Therapy, 2023)
OBJECTIVE: To determine if neck muscle strength and endurance are associated with concussion injuries in professional, male rugby players. Playing position, history of previous concussion, and age were also considered.